A Bioremediation Approach to Mercury Removal in a Shake Flask Culture Using Pseudomonas putida (ATCC 49128) - Abdul Aziz, Mohd Azoddein; Mani Malam, Ahmad; R. M., Yunus; Nik Meriam, Nik Sulaiman (OMICS International, 2016)
Mercury is one of the most poisonous elements found on earth bonded to sulfhydryl groups of enzymes and proteins, thereby inactivating vital cell functions. Indeed this has drawn the attention of many environmental researchers who have been attempting through various mean to expunging mercury from these contaminated medium. Biological approach provided a satisfactory outcome in the clean-up of mercury contaminated soil and water due to its high potential for greater performance, environment friendliness and cost effectiveness. Mercuryresistant bacterial strain (P. putida ATCC 49128), was experimented on its potential to grow and reduce mercury to a permissible level under optimum conditions of nutrient, pH and other related physical factors in an incubator shake flask. It was observed that P. putida displayed a usual growth pattern when tried at low level mercury concentration of 1.0 µM, 6.0 µM and 19.0 µM, by exponentially growing during the first 4 hours of inoculation, but drastically decreased by the end of 24 hours’ time. This was indicated by the mercury removal rate of 99.0%, 99.83% and 98.58% in the three mercury concentrations used. Also, under the same optimum condition of growth, mercury concentration of 1000 µM was reduced by 92.0% after the first initial 1 hour to 98.0% at the end of 28 hour study. Comparably, similar trend was also observed when P. putida was used as bioaugmented organism to treat mercury contaminated samples from two petroleum industry based wastewater. A reduction rate of 84% was observed at the initial first 4 hours to about 90.5% after 96 hour experiment for plant P1 wastewater. While results from wastewater plant P2 indicated reduction rate of 97.2%, followed by 94.09% and lastly 56.8% respectively. The result affirmed the ability of this strain to optimally utilize the optimal conditional factors to grow and reduce mercury concentration overwhelmingly within a shortest time of less than 30 hours.